A Community-Based Leadership Development Program for First Nations Women: Revaluing and Honoring Women’s Strengths - K. Amanda Maranzan; Alice Sabourin; Christine Simard-Chicago (University of Western Ontario, 2013)
Over 400 First Nation women participated in leadership development workshops developed by First Nation women for First Nation women. We collected survey data and conducted focus groups and interviews with workshop participants to identify outcomes and determine barriers and resources to women in leadership. Outcomes of the workshop included increased perception of women as leaders, increased personal capacity, and encouragement to seek opportunities for formal and informal leadership positions. Family and home responsibility, community pressure, and lack of support were identified as barriers faced by women in leadership or considering leadership positions. This program represents an effort to empower women to participate in social, cultural, and political life within their communities and obtain equitable political representation.